PANGGILAN TUHAN DI DALAM HIDUP ORANG PERCAYA - Erwin; Rikardo P. Sianipar (The Way Jurnal Teologi dan Kependidikan, 2019)
The purpose of this research was to discuss about God's calling in the lives of Moses as individuals. Every people is searching for meaning and purpose of their lives on earth, but it is very ironic that even believers inside the church isn't aware of God's calțing in their lives and how to answer and fulfill it. This results in the church only as a community of religious group alike with every other religion, without any difference or significant impact as the body of Christ. The forms of research are qualitative and observation, and from the result, it is concluded that God's calling is given to the believers in a common way, so each of the believer is supposed to accept and receive it along with a divine guidance that will lead their lives to fulfil it, with requirement of paying attention to God and His Glory. That God's calling isn't given only to certain believer. Every believer in Christ has a specific calling and role to be acted for God's glory. With the guidance of The Holy Spirit, they are enabled to fulfil the calling in each of their lives.